Regulatory variants in a novel distal enhancer regulate the expression of CYP3A4 and CYP3A5 - Joseph M. Collins; Adaeze C. Nworu; Somayya J. Mohammad; Liang Li; Chengcheng Li; Chuanjiang Li; Ethan Schwendeman; Mattew Cefalu; Mahmoud Abdel‐Rasoul; Jessie W. Sun; Sakima A. Smith; Danxin Wang (Wiley, 2022)
Abstract The cytochrome P450 3As (CYP3As) are abundantly expressed in the liver and metabolize many commonly prescribed medications. Their expression is highly variable between individuals with little known genetic cause. Despite extensive investigation, cis‐acting genetic elements that control the expression of the CYP3As remain uncharacterized. Using chromatin conformation capture (4C assays), we detected reciprocal interaction between a distal regulatory region (DRR) and the CYP3A4 promoter. The DRR colocalizes with a variety of enhancer marks and was found to promote transcription in reporter assays. CRISPR‐mediated deletion of the DRR decreased expression of CYP3A4, CYP3A5, and CYP3A7, supporting its role as a shared enhancer regulating the expression of three CYP3A genes. Using reporter gene assays, we identified two single‐nucleotide polymorphisms (rs115025140 and rs776744/rs776742) that increased DRR‐driven luciferase reporter expression. In a liver cohort (n = 246), rs115025140 was associated with increased expression of CYP3A4 mRNA (1.8‐fold) and protein (1.6‐fold) and rs776744/rs776742 was associated with 1.39‐fold increased expression of CYP3A5 mRNA. The rs115025140 is unique to the African population and in a clinical cohort of African Americans taking statins for lipid control rs115025140 carriers showed a trend toward reduced statin‐mediated lipid reduction. In addition, using a published cohort of Chinese patients who underwent renal transplantation taking tacrolimus, rs776744/rs776742 carriers were associated with reduced tacrolimus concentration after adjusting for CYP3A5*3. Our results elucidate a complex regulatory network controlling expression of three CYP3A genes and identify two novel regulatory variants with potential clinical relevance for predicting CYP3A4 and CYP3A5 expression.